Zbigniew Herbert, Zygmunt Freud, psychoanaliza, psychologia głębi, świadomość, podświadomość = Zbigniew Herbert, Sigmund Freud, psychoanalysis, depth psychology, consciousness, unconsciousness - Butewicz, Walery (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
This article analyses Zbigniew Herbert`s attitude towards psychoanalysis. The legacy of the Polish poet is prevalent among literary scholars. However, until now - as far as I know - no work has been written that would analyse Herbert`s work in the context of psychoanalysis.
Keywords: Herbert, Zbigniew (1924-1998); Freud, Zygmunt (1856-1939); psychoanaliza; psychologia głębi; świadomość; podświadomość; Freud, Sigmund (1856-1939); psychoanalysis; depth psychology; consciousness; unconsciousness